Keragaman Bulu Babi (Echinoidea) di Perairan Pantai Pulau Merah Pesanggaran Banyuwangi - Aimatuzzahro Aimatuzzahro; Agus Sufajar; N. Nurchayati (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2020)
Echinoidea has found in many marine defferences. This invertebrates were usually live in individualisia or in groups. They are live in rough substrate like rock and coastal but there are small group of echinoidea has live in sandy and muddy subtrate. The purpose of this research was to obtain the diversity ofechinoideain pulau merah shore Banyuwangi this research has been done in july 2016. This research used transek quadrat methode, divide 3 station. Station 1 lie down in side bouder of cea water, station 2 lie down in the middle of sea water and station 3 lie down prorude from sea water. In each station divide in 3 transeks and every transecs there were 3 plot. The result of this research showed there were 4 luind of echinoidea, Trineustes gratilla, Echinometra mathaei, Diadema sitosum, Sea urchin. the most many quantities of echinoidea species that found al most in all of the station was Echinometra mathaei the most hig herst diversity indees was Trineustes gratilla in station 2 (H’=1) in station 3(H’=1). In station 3 (H’=1). The most highast dominancy andecs was Echinometra mathaei in station 2 (D=0,664)